Sex differences of language abilities of preschool children with autism spectrum disorder and their anatomical correlation with Broca and Wernicke areas - Zhang, Yun; Qin, Bin; Wang, Longlun; Chen, Jie; Cai, Jinhua; Li, Tingyu (Frontiers in Pediatrics, 2022)
Objectives: People with autism spectrum disorder (ASD) often have language difficulties. This study focuses on whether there are sex differences in language ability in children with ASD, and aimed to analyze whether such differences may arise from developmental imbalances in the anatomical structures of Broca and Wernicke areas. Methods: The language development quotient (DQ) scores of Gesell Developmental Scale (GDS) and the scores of language communication of Childhood Autism Rating Scale (CARS) were used to judge the language ability, and FREESURFER software extracted the anatomical structures of Broca and Wernicke areas on 3DT1 sequences. We analyze the correlation between the anatomical structure of Broca/Wernicke areas and language abilities assessments. Results: The study initially included 44 cases of ASD, with 36 males (81.8 %) and 8 females (18.2 %), the age range was 24 to 72 months. Males have better language abilities than females. Specifically, the males GDS verbal DQ was significantly higher than females (56.50 ± 18.02 vs. 29.23 ± 6.67, P < 0.001). Broca thickness-L was positively correlated with verbal DQ scores in GDS (r = 0.382, P = 0.011) and was lower than grade 2 and 3 on the CARS verbal communication grade 4 (5.76 ± 0.17 vs 6.21 ± 0.30 & 6.11 ± 0.35), with statistically significant differences between groups (P < 0.05). Conclusion: There were sex differences in the language abilities of preschoolers with ASD, and this difference may be due to an imbalance development of certain structures in Broca and Wernicke areas, especially Broca area.